3D Reconstruction of a Nuclear Reactor by Muon Tomography: Structure Validation and Anomaly Detection - Baptiste Lefevre; Julien Vogel; Héctor Gomez; David Attié; Laurent Gallego; Philippe Gonzales; Bertrand Lesage; Philippe Mas; Daniel Pomarède (PRX Energy)
Muon tomography is a consolidated technique to investigate the internal components of high-opacity objects. With the use of detectors with high angular and spatial resolution (usually referred to as “muon telescopes”), the track reconstruction of the atmospheric muons after they have crossed the object provides muography images, also called “muon radiographs.” This work presents the muography (or muon radiography) reconstruction of a French historical UNGG (natural-uranium, graphite, and gas) nuclear reactor: the G3 reactor, located at CEA Marcoule. A measurement campaign involving 46 points of view below the reactor was conducted, providing a set of muography images. The method to analyze these muographies is detailed here. Besides, a method to combine these images to provide three-dimensional (2D) tomography of the reactor is also presented. After a general description of the project, all the methods performed to reconstruct and analyze muographies and the 3D reconstruction are presented. It comprises different tools based on data augmentation and machine learning, which proved to be very efficient on simulated data and increase the quality of the experimental data analysis. All these methods were evaluated with a set of synthetic data, providing a precise evaluation for better identification of the associated systematics. Finally, all the described methods were applied to the experimental data, leading to a full characterization of the reactor, in both two dimensions and three dimensions, and the identification of some discrepancies between the reactor actual structure and the original model. These anomalies are discussed, showing the potential of the technique to evaluate the internal structure of a nuclear reactor. This could have potential applications during the decommissioning phase and the dismantling phase of different kinds of nuclear installation.